The Prentice Hall self-assessment library - Robbins, Stephen P. (Upper Saddle River, NJ : Prentice Hall, 1999)
Includes 45 exercises to help you learn more about yourself and how you relate to others
System requirements (Windows): Pentium processor-based PC; 16 MB RAM (24 for Windows NT); 12 MB hard disk space; Windows 3.1, 95 or NT; Quicktime 2.1.2 or later; 4X CD-ROM drive; 256 color monitor; sound capabilities
System requirements (Macintosh): 8 MB RAM; 2.5 MB hard disk space; System 7.1.2 or later; Quicktime 2.5 or later; 4X CD-ROM drive; 256 color monitor; sound capabilities
Keywords: Self-evaluation